The tight grip of a debt based global economy: A study on banking regulation and the implementation of the Basel II Accord in Portugal - Silva, Jonathan Coelho Brum da (2010)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Management from the NOVA – School of Business and Economics